Film availability and diversity in large Croatian public libraries in relation to the IMDb list (Libellarium: journal for research in the field of information and related sciences, 2021)
Objective. The primary objective of this paper was to examine the extent to which the highest ranked films by the viewers, according to the Internet Movie Database (IMDb), are represented in the collections of the Public Library of Rijeka, Public Library of Marko Marulić in Split and the Zagreb Public Libraries. Another objective was to gain insight about the diversity of films from this list which are available in the libraries - the diversity related to the countries in which the films from the IMDb list were produced and the time periods in which they were produced.Methodology. The checklist method was used. The records from the catalogues of selected libraries were compared with the list of best films according to the users of the important Internet Movie Database portal, one of the most important web sources of film information. The research data were collected in 2021.Findings. The findings show that the libraries surveyed have approximately 50% to about 70% of films from the IMDb list in their collections. It was established that, in their collections,  the libraries are considerably more likely to have films from the USA that are on the IMDb list than films from other countries that are on the same list. In terms of the time period of film production, there are no significant discrepancies between the films from the IMDb list that are in the libraries and the films on the IMDb list itself.Practical implications. The paper contains proposals of activities that can support the creation of diverse film collections.Originality/Value. The paper emphasizes the importance and possibilities of strengthening diverse film collections. It presents and explores a topic that is rarely represented in the literature.Keywords: cultural diversity, film collections, Internet Movie Database (IMDb), public libraries
Keywords: Internet movie database (IMDb); cultural diversity; film collections; public libraries